(untitled) (Journal of Madenat Alelem, 2024)
Ensuring the security of multimedia information, such as images, is essential due to the rapid development of information technology, so various image encryption algorithms have been proposed to ensure privacy and prevent improper behaviour. This paper presents a proposed model called Multi-Layer Encryption Net (MLE-Net) to encrypt the image based on using a multi-layer net to code the image and modify the Blum-Blum-Shub pseudo-random number generator to generate the keys used in the encryption process. The proposed method is organized into two stages: the first stage is plain-image data pre-processing, and the second stage divides the used image into blocks to be input for a multi-layer encryption network. The proposed method uses secure keys generated by the Modified Blum-Blum-Shub (MBBS) random number generator to improve its accuracy, reduce the complexity, and modify its control parameters to maintain data privacy efficiently and accurately. The outcomes show that the suggested approach successfully provides secure information delivery.